Kajian Etnobotani Jenis-Jenis Bambu Sebagai Bahan Perlengkapan Rumah Tangga dan Konstruksi di Kabupaten Lombok Barat - Siskawati; Kurniasih Sukenti (The Ethnobiological Society of Indonesia, 2021)
Bamboo is a clumping plant, and distributed in tropics, subtropic and temperate regions. This study aimed to explore ethnobotanical aspects related to bamboo as a household handicraft and construction material. The selection of respondent used Snowball Sampling, while sampling areas were selected purposively. Data were analyzed qualitatively and quantitatively based on interviews, reported use, index of cultural significance, and fidelity level. The result showed that there were six species of bamboos used as materials for household crafts and construction, i.e. treng tutul (Bambusa maculata), treng tali (Gigantochloa apus), treng galah (Gigantochloa atter), treng dendeng (Bambusa vulgaris), treng bilok (Schizostachyum jaculans), dan treng betung (Dendrocalamus asper). The use of bamboo in household crafts was divided into eight categories, namely kitchen utensils, furnitures, room decorations, musical instruments, rituals’ tools, farming tools, art tools, and other kitchen utensils, meanwhile for the construction material was divided into three categories, namely: building construction, agricultural construction, and transportation tools. Several issues related to the uses of bamboo, especially as household crafts and construction, in West Lombok Regency were conservation, sosio-cultural, economic, and constraints in cultivation.